Corporate Taxes, Profit Shifting and the Location of Intangibles within Multinational Firms - Matthias Dischinger; Nadine Riedel (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
Intangible assets are one major source of profit shifting opportunities due to a highly intransparent transfer pricing process. Our paper argues that multinational enterprises (MNEs) optimize their profit shifting strategy by locating shifting–relevant intangible property at affiliates with a low statutory corporate tax rate. Using panel data for European MNEs and controlling for unobserved time–constant heterogeneity between affiliates, we find that the lower a subsidiary's tax rate relative to other affiliates of the multinational group the higher is its level of intangible asset investment. This effect is statistically and economically significant, even after controlling for subsidiary size and accounting for a dynamic intangible investment pattern.
urn:nbn:de:bvb:19-epub-4450-0
Keywords: H25; F23; H26; C33; 330; corporate taxation; multinational enterprise; profit shifting; intangible assets; micro level data; Gewinnverlagerung; Immaterielle Werte; Standortwahl; Multinationales Unternehmen; Unternehmensbesteuerung; Steuerwirkung; Schätzung; Europa